2020
DOI: 10.3390/membranes10120440
|View full text |Cite
|
Sign up to set email alerts
|

Size of Cells and Physicochemical Properties of Membranes are Related to Flavor Production during Sake Brewing in the Yeast Saccharomyces cerevisiae

Abstract: Ethyl caproate (EC) and isoamyl acetate (IA) are key flavor components of sake. Recently, attempts have been made to increase the content of good flavor components, such as EC and IA, in sake brewing. However, the functions of EC and IA in yeast cells remain poorly understood. Therefore, we investigated the effects of EC and IA using cell-sized lipid vesicles. We also investigated lipid vesicles containing EC and/or caproic acid (CA) as well as IA and/or isoamyl alcohol (IAA). CA and IAA are precursors of EC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(62 citation statements)
references
References 36 publications
3
59
0
Order By: Relevance
“…The clearest morphological changes were detected during the breeding of K7GE41. The K7GE41 cells became obviously larger ( Figure 7 C), in good agreement with the observation that the sake yeast strain producing a sweet ginjo aroma was large [ 32 ]. In addition, K7GE41 exhibited morphological changes, such as an increased proportion of cells with delocalized actin patches, increased G2 cells, and nuclear localization in mother cells ( Figure 7 C).…”
Section: Resultssupporting
confidence: 87%
“…The clearest morphological changes were detected during the breeding of K7GE41. The K7GE41 cells became obviously larger ( Figure 7 C), in good agreement with the observation that the sake yeast strain producing a sweet ginjo aroma was large [ 32 ]. In addition, K7GE41 exhibited morphological changes, such as an increased proportion of cells with delocalized actin patches, increased G2 cells, and nuclear localization in mother cells ( Figure 7 C).…”
Section: Resultssupporting
confidence: 87%
“…Previously, our team had measured the concentration of such flavor molecules in sake . Therefore, the actual concentration was shown as an example of the concentration of such flavors that we reported previously; the actual concentration on the sake was 75, 16, and 100 μM for EC, IA, and IAA, respectively . This study is the first to report the dynamic shape changes induced by sake flavor molecules; 2 mM flavor solution was used with the same concentration and compared with glucose as the positive control solution.…”
Section: Resultsmentioning
confidence: 72%
“…The membrane properties are according to cell, organism, and membrane type . Studies of actual yeast cells reported that cell size differences corresponded to flavor production. ,, Morphological change of liposomes has received considerable attention recently, for example, the morphological change phase diagram is formed by the balance between the surface area and the encapsulation volume in the cell model. , It is well analyzed that the resulting excess surface area and deformation of liposomes due to osmotic pressure make the internal water escape to the surface to reduce the volume, increase the surface area of membrane lipids via isomerization, and so on. Some studies have shown that membrane deformation occurs because the area of the membrane increases due to stimuli such as heat, and excess surface area is created while maintaining the internal volume. ,,, It has also been reported that liposome transformation is caused by a specific molecular interaction such as detergent , or polyphenol , with membrane lipid molecules. Recently, the impact of solvent selection on the microfluidic production of liposomes was reported .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations